Front Matter Vol. 13 No. 1 2020 - Statistika, Media (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2020)
Cover dan Daftar Isi Media Statistika Vol. 13 No. 1 Juni 2020